PBL Facilitator / Nurul Sufiani Ahmad - Nurul Sufiani, Ahmad (2004)
The traditional learning method, lecture-based learning that's still dominating learning method not only Malaysia, but almost everywhere in the world, can no longer ensure student's career stability in real world after education despite high academic achievement. In lecture-based learning or LBL, students usually tend to memorize information that the teachers feed to them for examination purpose without really understanding the meaning of the facts. This scenario won't guarantee students' readiness to face real problems in real world, a they won't be able to apply their knowledge in a more real-life context. Problem-based learning (PBL) however encourages students to learn how to solve real-life problems.It's learning method where students work in small groups with minimal help from facilitator and collaborate to analyse a given scenario and analyse it to identify the problems and then provide the solution. It's a much better way to make students really understand what they learn, why they learn and how to apply what the learn in real life. PBL discussions however, are always deterred or not fully effective because of different factors, such as uncomportable environment like hot temperature, crowded space, too noisy, uncomportable chairs and etcetera. Even if the discussions are held outside class hours, then there's the matter of adjusting members' schedule, additional costs in terms of energy and time, external distractions like chats and many others. As it is, the building of a web-based system that manages online PBL classroom will solve this problem. Named PBL Facilitator, it allows students to have a comfortable discussion environment, at students' and lecturers' choosing and cost.